PET Imaging a MPTP-Induced Mouse Model of Parkinson’s Disease Using the Fluoropropyl-Dihydrotetrabenazine Analog [18F]-DTBZ (AV-133) - Toomey, James S.; Bhatia, Shilpa; Moon, La’Wanda T.; Orchard, Elysse A.; Tainter, Kerrie H.; Lokitz, Stephen J.; Terry, Tracee; Mathis, J. Michael; Penman, Andrew D. (PLOS ONE, 2012)
Parkinson’s disease (PD) is characterized by the loss of dopamine-producing neurons in the nigrostriatal system. Numerous researchers in the past have attempted to track the progression of dopaminergic depletion in PD. We applied a quantitative non-invasive PET imaging technique to follow this degeneration process in an MPTP-induced mouse model of PD. The VMAT2 ligand 18F-DTBZ (AV-133) was used as a radioactive tracer in our imaging experiments to monitor the changes of the dopaminergic system. Intraperitoneal administrations of MPTP (a neurotoxin) were delivered to mice at regular intervals to induce lesions consistent with PD. Our results indicate a significant decline in the levels of striatal dopamine and its metabolites (DOPAC and HVA) following MPTP treatment as determined by HPLC method. Images obtained by positron emission tomography revealed uptake of 18F-DTBZ analog in the mouse striatum. However, reduction in radioligand binding was evident in the striatum of MPTP lesioned animals as compared with the control group. Immunohistochemical analysis further confirmed PET imaging results and indicated the progressive loss of dopaminergic neurons in treated animals compared with the control counterparts. In conclusion, our findings suggest that MPTP induced PD in mouse model is appropriate to follow the degeneration of dopaminergic system and that 18F-DTBZ analog is a potentially sensitive radiotracer that can used to diagnose changes associated with PD by PET imaging modality.